Cytochrome P450 monooxygenase CYP53 family in fungi : Structural analysis of CYP53A and its redox partner from the thermophilic fungus Thielavia terrestris - Jawallapersand, Poojah (Bloemfontein: Central University of Technology, Free State, 2015)
Cytochrome P450 monooxygenases (CYPs or P450s) are heme-thiolate proteins distributed across biological kingdoms. P450s show multiple and diverse catalytic activity on a wide range of substrates, and as such the use of these enzymes have been prompted in various areas such as the production of human valuable chemicals, pharmaceutical compounds, antibiotics, fragrances and the degradation of xenobiotic compounds. If P450s are to be used on a large-scale production, it is imperative that they are able to resist extreme industrial conditions, including thermostability. Considering the fact that P450s are weak and less stable enzymes, research has focused on identifying thermostable P450s. Furthermore, P450s have been used as a drug target against pathogens. However, a study revealed that pathogens are developing drug resistance against currently available drugs. To tackle and address this emerging dilemma to drug resistance, novel drug targets need to be discovered and identified. The current study is the first of its kind that focuses on two aspects, which are identifying a common alternative anti-fungal drug target and structural characterization of thermostable P450 CYP53A and its redox partner cytochrome P450 reductase (CPR) from biomass-degrading thermophilic ascomycete Thielavia terrestris. This study also marks the beginning of our understanding on thermostable P450s from eukaryotes. Part of the study has been published as an article in PLoS ONE journal (impact factor 3.5). Below are the details of the manuscript:
Thesis
Keywords: Cytochrome P-450 CYP53 - Therapeutic use; Thielaviopsis terrestris - Therapeutic use; Fungi - Therapeutic use; Antifungal agents